2020
DOI: 10.1001/jamaoncol.2020.2054
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exercise Intolerance With Emotional Distress, Attainment of Social Roles, and Health-Related Quality of Life Among Adult Survivors of Childhood Cancer

Abstract: IMPORTANCEExercise intolerance is associated with increased risk for morbidity and mortality in childhood cancer survivors. However, an association between exercise intolerance and psychosocial outcomes has not been fully explored.OBJECTIVE To examine the associations between exercise intolerance and emotional distress, attainment of social roles, and health-related quality of life in childhood cancer survivors. DESIGN, SETTING, AND PARTICIPANTS A cross-sectional study including 1041 adult survivors of childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 70 publications
0
25
0
4
Order By: Relevance
“…As a group, survivors of CAYA cancers are at risk for lower educational achievement with respect to comparison groups (Level C), 17‐62 and fewer survivors than comparisons have a university or college education (Level B) 17,18,21,22,24‐27,29,31,35‐37,47,49,58,63‐69 . Specifically, we found 46 studies that compared educational achievement in survivors to that of siblings, peers, or the general population 17‐62 .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…As a group, survivors of CAYA cancers are at risk for lower educational achievement with respect to comparison groups (Level C), 17‐62 and fewer survivors than comparisons have a university or college education (Level B) 17,18,21,22,24‐27,29,31,35‐37,47,49,58,63‐69 . Specifically, we found 46 studies that compared educational achievement in survivors to that of siblings, peers, or the general population 17‐62 .…”
Section: Resultsmentioning
confidence: 80%
“…In comparison with control groups, the educational attainment of survivors was lower in 19 studies (13 independent study samples), 17,18,26,32,35‐37,49‐59 higher in 4 studies, 21,22,30,33 and not significantly different in 23 studies (20 samples) 19,20,23‐25,27‐29,31,34,38‐48,61,62 (Supporting Table 11). Among 23 studies that evaluated the proportion of university/college graduates among survivors versus comparisons 17,18,21,22‐27,29,31,35‐37,47,49,58,63‐69 the proportion was lower in 12 studies (7 samples), 17,18,26,35‐37,49,58,63,66,67,69 higher in 1 study, 21 and not significantly different in 10 studies (6 samples) (Supporting Table 11). 22,24,25,27,29,31,47,64,65,68 Survivors of CNS tumors were at increased risk for lower educational achievement 26,57,60,61 and for not getting a college/university degree 37,58,63,67 (both Level B; Table 1 and Supporting Table 10).…”
Section: Resultsmentioning
confidence: 98%
“…The mean time after allo-HSCT in our cohort was more than 5 years; maybe HRQL was lower closer to allo-HSCT. Further studies are needed to see whether an exercise intervention can improve HRQL, as in former studies decreased physical functioning has been shown to impact quality of life in survivors of childhood cancer [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrate, though, that regular physical activity can improve the cardiovascular risk profile in pediatric cancer survivors [12] and regular exercise training during and after cancer treatment positively affects body composition, flexibility, cardiorespiratory fitness, muscle strength, and health-related quality of life [13]. Finally, exercise capacity and physical activity are closely related to health-related quality of life in healthy children [14] but data suggests that this applies even more to survivors of childhood cancer [8,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…These attenuate the immune system; reduce the QoL and GH [12,13]. Various measures are taken to achieve physical and GH and increase public health, including sports and recreational activities.…”
Section: Introductionmentioning
confidence: 99%